Evaluation of technique of dry powder inhaler and metered dose inhaler in chronic obstructive pulmonary disease or asthma patients - Prasad Acharya, Chandra; Muhammad, Gulam; Bastola, Sanjib; Yadav, Alok; Jha, Suprabha (Journal of Chitwan Medical College, 2024)
Background: Chronic Obstructive Pulmonary Disease (COPD) and asthma are common respiratory conditions managed primarily via inhaled therapies. Improper inhalation techniques can lead to therapeutic failure and worsen disease outcomes. This study aimed to assess the effectiveness of an intervention to improve inhalation techniques in COPD and asthma patients using rotahaler devices. Method: The study was conducted at the pulmonology outpatient department of Manipal Teaching Hospital from March 2024 to September 2024, following ethical approval. Patients with COPD or asthma using metered-dose inhalers (MDIs) or dry powder inhalers (DPIs) and a follow-up duration of at least one month were included. Baseline technique scores were recorded using a pre-defined scoring chart. An intervention, including counselling and physical demonstration, was provided, and scores were reassessed immediately and at follow-up. Data were analysed using SPSS. Result: A total of 109 participants were enrolled. At baseline, 85 participants (78%) achieved perfect MDI scores. Following the intervention, nearly all participants (23/24) who initially scored less than perfect achieved a full score. After follow up, 19 of these participants (82.6%) maintained their improved performance, while 5 (17.4%) experienced minor declines. Conclusion: The intervention significantly improved inhalation techniques, with most participants retaining the improvement after one month. Periodic reinforcement may benefit a minority. Common errors in steps such as mouthpiece placement and breath-holding highlight areas for targeted education to sustain effective inhalation techniques.